Evidences on Irrational Anti-Microbial Prescribing and Consumption among COVID-19 Positive Patients and Possible Mitigation Strategies: A Descriptive Cross Sectional Study (Bangladesh Journal of Infectious Diseases, 2020)
Background: Increased antimicrobial consumption has increased the burden on worsening situation of antimicrobial resistance throughout the world.Objective: The purpose of this study was to assess the practice of irrational antibiotic prescribing and consumption among COVID-19 positive patients of Bangladesh and its possible impact on existing AMR.Methodology: This was a cross-sectional study conducted among SARS-CoV-2 positive patients from a tertiary COVID-19 PCR testing center in Dhaka between 10th July 2020 and 20th July 2020. A validated questionnaire was used to gather data. Ethical approval was obtained. A total of 100 participants through random sampling was selected.Results: A total of 100 COVID-19 RT-PCR positive patients were participated in this study: 96% had mild symptoms, fever (81.0%) was the most common presenting symptoms, 45.0% patients did not consult with physicians even after knowing their positive test results and reported self medicating with antibiotics, and 36.0% were treated with multiple antibiotics and antiviral at a time. Azithromycin (46.0%), Ivermectin (22.0%) and doxycycline (21.0%) were the antibiotics most used, which were mainly obtained from local retail pharmacies.Conclusion: Practice of irrational antibiotic prescribing and self medication is relatively high among COVID-19 positive participants.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S3-S7